Fine Tuning of Colloidal CdSe Quantum Dot Photovoltaic Properties by Microfluidic Reactors. (20th December 2016) - Jeong, Da-Woon; Park, Ji Young; Kim, Taek-Soo; Seong, Tae-Yeon; Kim, Jae-Yup; Ko, Min Jae; Kim, Bum Sung
Graphical abstract: Highlights: Continuous microfluidic reactors were constructed for the synthesis and photoelectrochemcial application of CdSe QDs. Spectral range and quantum yield of QDs were finely tuned by controlling the flow rates of precursor solutions and solvents. Conversion efficiency of QDSCs was enhanced by 19% with the increase in QY from 15.4% to 23.2%. Decreased surface states of QDs led to the reduced electron recombination in QDSCs. Abstract: Colloidal quantum dots (QDs) are attractive materials for application in photovoltaic and photoelectrochemical devices, due to their unique properties including band energy tunability, high absorption coefficient and multiple exciton generation. Here, we construct continuous and automated microfluidic reactors for the synthesis of CdSe QDs, and apply the synthesized QDs to the QD-sensitized solar cells (QDSCs) as a photosensitizer. The spectral range, quantum yield (QY) and surface states of QDs are facilely and finely tuned by controlling the flow rates of precursor solutions and solvents in the microfluidic reactors. The photovoltaic and photoelectrochemical performances of QDSCs are strongly affected by both the spectral range and QY of CdSe QDs. In particular, the conversion efficiency is enhanced by about 19% with the increase in QY from 15.4% to 23.2%, at the same spectral range. Furthermore, the enhanced surface purity of QDs by modified synthetic condition leads to the reduced electron recombination in the QD-sensitized TiO2 electrodes, which is confirmed by electrochemical impedance analysis. This study demonstrates the great potential of microfluidic system for the synthesis QDs and their application in photoelectrochemical solar cells.